Use of electronic cigarettes and associated factors among thai vocational students: An institution-based cross-sectional study - Jeeraphat Rattanachompoo; Chakkraphan Phetphum; Narongsak Noosorn (Wolters Kluwer Medknow Publications, 2024)
Introduction: The use of young electronic cigarettes (e-cigarettes) is increasing worldwide, including in Thailand, where there are strict regulations governing the availability of e-cigarettes. This study explored e-cigarette use among vocational students and associated factors in Thailand. Methods: We enrolled 1150 students from six vocational institutions in the upper northern region of Thailand using a multistage design and gathered the data through a self-administered questionnaire. Multivariate logistic regression models were used to examine the variables and their association with e-cigarette use. Results: Most of the participants (66.5%) were male, and the average age was 17 ± 1.7 years. The prevalence of e-cigarette use in the past 30 days was 18.4%. We found that the perceived price of e-cigarettes being affordable (adjusted odds ratio [AOR] = 1.7, 95% confidence interval [CI]: 1.0-2.8), traditional cigarette smoking in the past year (AOR = 3.5, 95% CI: 2.4-5.1), a high positive attitude toward e-cigarettes (AOR = 2.6, 95% CI: 1.7-3.9), alcohol consumption in the past year (AOR = 1.8, 95% CI: 1.1-2.8), having close friends who used e-cigarettes (AOR = 4.4, 95% CI: 3.1-6.3), and having low self-esteem (AOR = 1.6, 95% CI: 1.1-2.3) were significantly associated with e-cigarette use in the past 30 days. Conclusion: The use of e-cigarettes is prevalent among Thai vocational students, suggesting that continued maintenance of the enforcement policy on banning the importation of e-cigarettes into the country is thus needed. Furthermore, the government should improve law enforcement, especially against online marketing, and strengthen school-based anti-smoking programs.